High thermal conductivity preformed solder sheet and preparation method thereof
By adding a metal load to a single -wall carbon nanot barrier and alloy reinsurance in the prefabricated welding sheet, the problem of low heat and cooling capacity of existing welding slices and low mechanical properties, significantly improved the mechanical performance of the welding sheet And thermal conductivity and reduce production costs.
Patent Information
- Application Number
- CN202310351018.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing preformed welding sheets have low thermal conductivity and low mechanical properties, making it difficult to meet the high requirements of electronic packaging materials in the electronics industry.
By adding a metal load to a single -wall carbon nanot barrier to the prefabricated welded sheet, it is synergistic with the alloy reinsurance to improve the thermal guidance, welding performance, and mechanical performance of the welding sheet. Sexual and mechanical properties.
It significantly improves the mechanical performance and thermal conductivity of the pre -formed welding sheet, enhances the intensity of the welding interface, improves the intensity and toughness of the weld, and reduces the crack sensitivity of the weld, and reduces the production cost of the welding sheet.
Smart Images

Figure CN116135416B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preformed solder sheets, and in particular to a high thermal conductivity preformed solder sheet and a preparation method thereof. Background Art
[0002] Due to the rapid development of the electronics industry, higher requirements are placed on the use of electronic packaging materials. They must have good mechanical properties, corrosion resistance, electrical insulation, high thermal conductivity, low expansion coefficient and other advantages. However, the traditional interconnection materials between chips and substrates have fatal defects of their own materials and are difficult to meet the requirements. Preformed solder sheets have a specific processing shape and are a new type of welding material, but their heat dissipation capacity is not high.
[0003] Carbon nanotubes (CNTs) are a new type of two-dimensional tubular carbon nanomaterials with extremely high elastic modulus and tensile strength, low density and thermal expansion coefficient, good toughness, high temperature resistance and chemical stability. The excellent mechanical properties of carbon nanotubes themselves, as well as dispersion strengthening and grain refinement can be used to improve the performance of preformed solder sheets and improve the thermal conductivity and heat dissipation capabilities of preformed solder sheets. However, there are no reports on adding carbon nanotubes to solder sheets to improve the thermal conductivity and heat dissipation capabilities of preformed solder sheets. Summary of the invention
[0004] The present invention provides a high thermal conductivity preformed solder sheet in order to solve the technical problems that the existing preformed solder sheet has low thermal conductivity and heat dissipation capabilities and low mechanical properties.
[0005] A second object of the present invention is to provide a method for preparing a high thermal conductivity solder preform.
[0006] To achieve the above first purpose, the technical solution adopted by the present invention is:
[0007] A high thermal conductivity preformed solder sheet, comprising a preformed solder sheet and a flux layer wrapped on the preformed solder sheet;
[0008] The alloy raw material of the preformed solder sheet is composed of the following components by weight percentage: 93.5-96.0% of tin, 0.3-1.0% of silver, 0.1-0.8% of copper, 0.1-0.2% of cerium, 0.2-0.7% of bismuth, 0.1-0.5% of gallium, 0.2-1.0% of antimony and 2.5-3.0% of modified carbon nanotubes;
[0009] The raw materials of the soldering flux layer are composed of the following components by weight percentage: 75-80wt% of rosin, 10-15wt% of activator, 2-3wt% of surfactant, 4-6wt% of thixotropic agent and 3-6wt% of antioxidant.
[0010] The modified carbon nanotubes are metal-loaded modified single-walled carbon nanotubes. By setting the metal-loaded modified single-walled carbon nanotubes and the alloy compounding synergistically, the thermal conductivity, welding performance and mechanical properties of the preformed solder sheet can be improved, the compatibility between the carbon nanotubes and the alloy is improved, and a very excellent effect is produced. The weldability of the preformed solder sheet can also be effectively improved. The addition of the modified carbon nanotubes can not only solve the floating problem of the single-walled carbon nanotubes, so that the drop toughness of the solder is improved, but also enhance the dispersibility of the carbon nanotubes in the solder alloy solder of the solder sheet, further improve the drop toughness of the solder joint, and the single-walled carbon nanotubes loaded by the metal are added into the alloy component, which can significantly improve the mechanical properties and thermal conductivity of the solder sheet. The addition of carbon nanotubes can enhance the bonding strength of the welding interface, improve the strength and toughness of the weld, and reduce the crack sensitivity of the weld.
[0011] Preferably, the metal in the metal-loaded modified single-walled carbon nanotubes includes any one of palladium, platinum and copper. More preferably, the metal is platinum. By loading carbon nanotubes with platinum metal, the alloy can be provided with good chemical stability and mechanical strength, and has excellent thermal conductivity.
[0012] Preferably, the method for preparing platinum-loaded single-walled carbon nanotubes comprises the following steps:
[0013] The complex of divinyl sulfide and chloroplatinic acid is placed in n-heptane and stirred to dissolve, and the single-walled carbon nanotubes are added and left to stand for 12-15 hours. The single-walled carbon nanotubes are filtered and placed in a 90°C oven for baking for 2-3 hours to obtain, more preferably, the mass ratio of the metal complex to n-heptane is 1:100, and the mass ratio of the single-walled carbon nanotubes to n-heptane is 3:5. The platinum ions are coordinated with the diethyl sulfide molecules through hybridization to form a stable structure, and can cooperate with the divinyl ether bond to form a stable complex with platinum. After being loaded on the carbon nanotubes, they are added to the welding sheet to improve their thermal conductivity.
[0014] Preferably, the particle size of the single-walled carbon nanotube is 1-2 nm. By selecting single-walled carbon nanotubes with smaller particle sizes, divinyl ether bonds can form complexes with metals. More preferably, the particle size is 2 nm.
[0015] Preferably, the activator is any one of isopropylamine hydrobromide, triethanolamine hydrobromide and monoisopropanolamine, and more preferably, the activator is monoisopropanolamine.
[0016] Preferably, the thixotropic agent is a combination of hydroquinone, dodecyl hydroxystearic acid and modified hydrogenated castor oil. More preferably, the thixotropic agent is a mixture of hydroquinone, dodecyl hydroxystearic acid and modified hydrogenated castor oil in a mass ratio of 2:1:3. Hydroquinone, dodecyl hydroxystearic acid and modified hydrogenated castor oil cooperate with each other to prevent the welding piece from collapsing, thereby preventing tailing, adhesion, collapse and the like during brazing.
[0017] Preferably, the antioxidant is any one of ethoxyquinoline, 2-ethyletherazole, and methylbenzotriazole. More preferably, the antioxidant is methylbenzotriazole.
[0018] Preferably, the surfactant is sodium dodecylbenzene sulfonate.
[0019] Preferably, the overall shape of the high thermal conductivity preformed solder sheet is square, circular, arc-shaped, ring-shaped, frame-shaped or strip-shaped.
[0020] In order to achieve the above second purpose, the technical solution adopted by the present invention is:
[0021] The method for preparing the high thermal conductivity preform solder sheet as described in any one of the above items comprises the following steps:
[0022] S1. Preparation of modified carbon nanotubes;
[0023] S2, weighing the above alloy components according to the weight percentage, melting and mixing, cooling to 450° C., adding the modified carbon nanotubes obtained in step S1, stirring for 20 to 30 minutes, continuously heating to 800° C., mixing for 5 to 10 minutes, and die-casting after cooling;
[0024] S3. Spray the flux evenly on the surface of the solder sheet obtained in step S2 and dry it to obtain a high thermal conductivity preformed solder sheet. The alloy components are first melted and mixed and then the temperature is lowered to 450° C., and then the carbon nanotubes are added and the temperature is continuously raised to 800° C. This is beneficial to the mixing of rare earth metal cerium and carbon nanotubes. The operation is simple, and a stable solder sheet can be formed with each component, thereby reducing the production cost of the solder sheet and having excellent application prospects.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. The high thermal conductivity preformed solder sheet provided by the present application can improve the thermal conductivity, welding performance and mechanical properties of the preformed solder sheet by setting the metal-loaded modified single-walled carbon nanotubes and the alloy compound synergistically, improve the compatibility between the carbon nanotubes and the alloy, produce very excellent effects, and effectively improve the weldability of the preformed solder sheet. The addition of modified carbon nanotubes can not only solve the floating problem of single-walled carbon nanotubes, so that the drop toughness of the solder is improved, but also enhance the dispersion of carbon nanotubes in the solder sheet alloy solder, further improve the drop toughness of the solder joint, and add the metal-loaded single-walled carbon nanotubes into the alloy component, which can significantly improve the mechanical properties and thermal conductivity of the solder sheet. The addition of carbon nanotubes can enhance the bonding strength of the welding interface, improve the strength and toughness of the weld, and reduce the crack sensitivity of the weld.
[0027] 2. The preparation method of the high thermal conductivity preformed solder sheet provided in the present application is to first melt and mix the alloy components and then cool the temperature to 450°C, and then continue to heat up to 800°C after adding carbon nanotubes. This can be beneficial to the mixing of rare earth metal cerium and carbon nanotubes. The operation is simple, and a stable solder sheet can be formed with each component, thereby reducing the production cost of the solder sheet and having excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for describing the embodiments are briefly introduced below.
[0029] Figure 1 It is a cross-sectional structural diagram of the high thermal conductivity preformed solder sheet of the present application. DETAILED DESCRIPTION
[0030] The specific technical scheme of the present invention is described below in conjunction with specific embodiments 1-3:
[0031] (1) Preparation of modified carbon nanotubes
[0032] Platinum loading: 1g of the complex of divinyl sulfide and chloroplatinic acid was placed in 100g of n-heptane and stirred to dissolve, and 60g of single-walled carbon nanotubes with a particle size of 2nm were added and allowed to stand for 12h. The single-walled carbon nanotubes were filtered and placed in an oven at 90°C for 2h to obtain platinum.
[0033] Copper loading: 1g of divinyl disulfide benzimidazolone copper complex was placed in 100g of n-heptane and stirred to dissolve, and 60g of single-walled carbon nanotubes with a particle size of 2nm were added, and the mixture was allowed to stand for 12h. The single-walled carbon nanotubes were filtered and placed in an oven at 90°C for 2h to obtain the product.
[0034] (2) Preparation of flux
[0035] Add 75wt% rosin into a container, heat to 120-140°C, and after it is dissolved, add 2wt% surfactant and stir until it is completely dissolved; keep the temperature at 120-140°C, add 5wt% thixotropic agent and stir until it is completely dissolved; lower the temperature to 60-80°C, add 3wt% antioxidant and 15wt% activator, stir for 40-60 minutes, and obtain liquid flux.
[0036] Embodiment 1:
[0037] S1. Weigh the above alloy components according to the weight percentage in Table 1, melt and mix, cool to 450° C., add the platinum-loaded modified carbon nanotubes obtained in step (1), stir for 20 to 30 minutes, continue heating to 800° C., mix for 5 to 10 minutes, and die-cast after cooling;
[0038] S2. Evenly spray the soldering flux obtained in step (2) onto the surface of the solder sheet obtained in step S1, and dry the solder sheet to obtain a high thermal conductivity preformed solder sheet.
[0039] Embodiment 2:
[0040] S1. Weigh the above alloy components according to the weight percentage in Table 1, melt and mix, cool to 450° C., add the platinum-loaded modified carbon nanotubes obtained in step (1), stir for 20 to 30 minutes, continue heating to 800° C., mix for 5 to 10 minutes, and die-cast after cooling;
[0041] S2. Evenly spray the soldering flux obtained in step (2) onto the surface of the solder sheet obtained in step S1, and dry the solder sheet to obtain a high thermal conductivity preformed solder sheet.
[0042] Embodiment 3:
[0043] S1. Weigh the above alloy components according to the weight percentage in Table 1, melt and mix, cool to 450° C., add the platinum-loaded modified carbon nanotubes obtained in step (1), stir for 20 to 30 minutes, continue heating to 800° C., mix for 5 to 10 minutes, and die-cast after cooling;
[0044] S2. Evenly spray the soldering flux obtained in step (2) onto the surface of the solder sheet obtained in step S1, and dry the solder sheet to obtain a high thermal conductivity preformed solder sheet.
[0045] Comparative Example 1
[0046] S1, weighing the above alloy components according to the weight percentage in Table 1, melting and mixing, cooling to 450° C., adding the copper-loaded modified carbon nanotubes obtained in step (1), stirring for 20 to 30 minutes, continuously heating to 800° C., mixing for 5 to 10 minutes, and die-casting after cooling;
[0047] S2. Evenly spray the soldering flux obtained in step (2) onto the surface of the solder sheet obtained in step S1, and dry the solder sheet to obtain a high thermal conductivity preformed solder sheet.
[0048] Table 1: Weight ratio of solder alloy powder components of Examples 1-3 and Comparative Example 1
[0049] Alloy composition Example 1 Example 2 Example 3 Comparative Example 1 tin 93.5 94.5 96 96 silver 1 0.5 0.3 1 copper 0.8 0.2 0.1 0.8 cerium 0.2 0.1 0.1 0.2 bismuth 0.7 0.2 0.2 0.7 gallium 0.3 0.5 0.1 0.3 antimony 1 1 0.2 1 Fullerene 2.5 3 3 -
[0050] The preformed solder sheets obtained in Examples 1-3 and Comparative Example 1 were subjected to performance tests according to the standard GB / T3651-2008 "Method for measuring thermal conductivity of metals at high temperatures" and the standard GBT228.1-2010 "Method for tensile test of metal materials at room temperature". The test results are shown in Table 2.
[0051] Table 2: Void rate test results of Examples 1-3 and Comparative Examples 1-2
[0052]
[0053] As can be seen from Table 2, the tensile strength and thermal conductivity of Comparative Example 1 slightly decrease by adding copper-loaded carbon nanotubes, but the overall performance is not affected. Therefore, the high thermal conductivity preformed solder sheet provided by the present application can improve the thermal conductivity, welding performance and mechanical properties of the preformed solder sheet by setting the metal-loaded modified single-walled carbon nanotubes and the alloy compound to cooperate with each other, improve the compatibility between the carbon nanotubes and the alloy, produce a very excellent effect, and can also effectively improve the weldability of the preformed solder sheet. The addition of modified carbon nanotubes can not only solve the floating problem of single-walled carbon nanotubes and improve the drop toughness of the solder, but also enhance the dispersion of carbon nanotubes in the solder sheet alloy solder, further improve the drop toughness of the solder joint, and the addition of metal-loaded single-walled carbon nanotubes into the alloy component can significantly improve the mechanical properties and thermal conductivity of the solder sheet. The addition of carbon nanotubes can enhance the bonding strength of the welding interface, improve the strength and toughness of the weld, and reduce the crack sensitivity of the weld. The preparation method is to first melt and mix the alloy components and then cool them to 450°C, and then continue to heat them to 800°C after adding carbon nanotubes. This can be beneficial to the mixing of rare earth metal cerium and carbon nanotubes. The operation is simple, and it can form a stable sheet with each component, reducing the production cost of the welding sheet, and has excellent application prospects.
[0054] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. High thermal conductivity preform solder sheet, characterized by: It comprises a preformed solder sheet (1) and a flux layer (2) coated on the preformed solder sheet (1); The alloy raw material of the preformed solder sheet (1) is composed of the following components by weight percentage: 93.5-96.0% of tin, 0.3-1.0% of silver, 0.1-0.8% of copper, 0.1-0.2% of cerium, 0.2-0.7% of bismuth, 0.1-0.5% of gallium, 0.2-1.0% of antimony and 2.5-3.0% of modified carbon nanotubes; The raw materials of the solder flux layer (2) are composed of the following components by weight percentage: 75-80wt% of rosin, 10-15wt% of activator, 2-3wt% of surfactant, 4-6wt% of thixotropic agent and 3-6wt% of antioxidant; The modified carbon nanotubes are metal-loaded modified single-walled carbon nanotubes; The metal in the metal-loaded modified single-walled carbon nanotubes is platinum; The method for preparing the modified carbon nanotubes comprises the following steps: The complex of divinyl sulfide and chloroplatinic acid is placed in n-heptane and stirred to dissolve, and single-walled carbon nanotubes are added. The mixture is allowed to stand for 12-15 hours. The single-walled carbon nanotubes are filtered and placed in an oven at 90° C. for 2-3 hours to obtain the product.
2. The high thermal conductivity solder preform according to claim 1, characterized in that: The particle size of the single-walled carbon nanotube is 2 nm.
3. The high thermal conductivity solder preform according to claim 1, characterized in that: The activator is any one of isopropylamine hydrobromide, triethanolamine hydrobromide and monoisopropanolamine.
4. The high thermal conductivity solder preform according to claim 1, characterized in that: The thixotropic agent is various combinations of hydroquinone, dodecyl hydroxystearic acid and modified hydrogenated castor oil.
5. The high thermal conductivity solder preform according to claim 1, characterized in that: The antioxidant is any one of ethoxyquinoline, 2-ethyletherazole and methylbenzotriazole.
6. The high thermal conductivity solder preform according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate.
7. The high thermal conductivity solder preform according to claim 1, characterized in that: The overall shape of the high thermal conductivity preformed solder sheet is square, circular, arc-shaped, ring-shaped, frame-shaped or strip-shaped.
8. The method for preparing a high thermal conductivity solder preform according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of modified carbon nanotubes; S2, weighing the above alloy components according to the weight percentage, melting and mixing, cooling to 450° C., adding the modified carbon nanotubes obtained in step S1, stirring for 20-30 min, continuously heating to 800° C., mixing for 5-10 min, and die-casting after cooling; S3, spraying the solder flux evenly on the surface of the solder sheet obtained in step S2, and drying, to obtain a high thermal conductivity preformed solder sheet.
Citation Information
Patent Citations
Carbon-nanotube-reinforced lead-free solder and preparation method thereof
CN102152018A
Graphene-modified low-temperature solder and preparation method thereof
CN111112881A
High-reliability preformed soldering lug and preparation method thereof
CN114669908A